Different Treatment of Olecranon Bursitis in Six Horses - Hayat, Ali; Han, M. Cengiz; Sagliyan, Aydin; Biricik, Halil Selcuk (Medwell Online, 2009)
The purpose of the study, reported here was to determine the outcome of various treatments for olecranon bursitis in horses. This study was carried out on horses (n = 6) with olecranon bursitis. All horses had a prominent swelling over the olecranon tuberosity. Four horses were treated medically using corticosteroid and peniciline combination. This treatment definitely treated 3 cases; 1 cases progressed to fibrosis and small knot remained at the region. Surgical treatment was carried out on 2 horses with olecranon bursitis (one of them bilateral olecranon bursitis). Surgery site of horses healed by primary intention and the owners of these horses were pleased with the cosmetic results. Surgical removal of bursitis was effective for the treatment of olecranon bursitis in horses. This technic provided more rapid healing and was more economical than conservative treatment.
Keywords: Bursitis; olecranon; horse; outcome; treatment; prominent swelling